Teaching approaches of Physical Education in higher education - Gošnik, Jelka (Array, 2011)
This paper approaches the physical-health educational field as a factor that supports development and revision of attitudes and conceptions of students at higher education institutions. It emphasizes the importance of recognition and respect for the initial anthropological status of freshmen enrolled in their study program for the programming of Physical Education programs in higher education, which is the last level of studies which includes compulsory Physical Education teaching. Physical Education is determined as a unique educational field with specific teaching forms and methods. The development of teaching practice at higher education institutions is viewed through the prism of its educational value in the time of the prevalence of a sedentary lifestyle and also from the point of view of a revision of one's system of values as well as students' success criteria. It also emphasizes the existence of pluralistic teaching approaches in kinesiological education which are based on the new education paradigm that places students and their individual biopsychosocial and cognitive characteristics in a center of educational process. The paper represents the results of research conducted at three higher education institutions specialized for humanities, social sciences and science and technology in the academic year 2009-10. This type of research was conducted systematically during the last ten years at the Faculty of Humanities and Social Sciences in Zagreb. In order to diagnose the initial anthropological status of every enrolled freshman we use a survey method which aids the creation of Physical Education teaching programs. The research has pointed out to a significant percentage of students at the Faculty of Humanities and Social Sciences in Zagreb who consider that in addition to a compulsory Physical Education teaching in form of exercises there should be a theoretical part of the course that would take the form of lectures containing academic units from the field of kinesiology in accordance with the specifics of their chosen study fields. As a result of all of this, an elective course entitled ''Man and sport'', based on interdisciplinary approach of Physical Education teaching at higher education institutions as well as interdisciplinary correlation was offered.